Message - Christine Joy Arquiza (Philippine Journal of Otolaryngology Head and Neck Surgery)
Happy Holidays! The Philippine Society of Otolaryngology-Head and Neck Surgery (PSO HNS) Board of Trustees congratulates the Editorial Board of the Philippine Journal of Otolaryngology – Head and Neck Surgery (PJO-HNS), headed by Dr. Jose Florencio Lapeña, Jr., on the publication of this issue. Dr. Lapeña has been the editor-in-chief of the PJO-HNS for the past 18 years, and it has grown in scope and stature under his leadership.